The Development of Tourism in the Republic of Tatarstan: An Investigation on Activities in Modern Fields - Galimova, Leysan; Galimov, Shamil’; Gerasimova, Ekaterina (Journal of History Culture and Art Research, 2018)
The development of tourism is an extremely important direction of the economy of Tatarstan, which affects all spheres of modern society, including culture and social life of the region. The exploration and introduction of new fields in the sphere of tourism promotes the main branches of the economy, forcing them to actively rebuild and introduce the latest technologies and compete in the world goods market. All these contribute to the inflow of investments into the economic segments. Each region tries to attract as many tourists as possible, for this purpose it is expedient to determine the main spheres and directions of activity involved in the development of the industry. The paper outlines the main activities for tourism industry organizations, identifies the main problems in the development of tourism, presents the developed certain recommendations for increasing the tourist flow to the republic. The region's successes in promoting the brand of the territory are noted. The role and importance of actualizing the region's identity in the development of tourism are defined. The role of the organization of cooperation between hospitality enterprises (tour operators and travel agencies, accommodation and catering facilities) under the guidance of the State Committee for Tourism is noted, as well as a description of new directions of tourism development in the Republic of Tatarstan is provided.